Diseño de un modelo de gestión administrativa para la reactivación económica dela empresa E.R & T. - Chávez, Katherin M. (2022)
The year 2020 has been difficult and atypical for most companies in the world because they experienced a considerable drop in their income, both from changes in consumption and sanitary restrictions implemented by the governments. The sudden appearance of the COVID-19 virus has caused deep changes in society and in the business environment in particular, in a context complex as the one we live in, which forces us to continually reconsider routines to survive.